Research priorities for maintaining biodiversity's contributions to people in Latin America. Issue 1 (8th August 2019) - Pearson, Richard G.; Martínez-Meyer, Enrique; Velázquez, Mercedes Andrade; Caron, Mercedes; Corona-Núñez, Rogelio O.; Davis, Katrina; Durán, América Paz; García-Morales, Rodrigo; Hackett, Talya D.; Ingram, Daniel J.; Díaz, Rafael Loyola; Lescano, Julián; et al.
Abstract : Maintaining biodiversity is crucial for ensuring human well-being. The authors participated in a workshop held in Palenque, Mexico, in August 2018, that brought together 30 mostly early-career scientists working in different disciplines (natural, social and economic sciences) with the aim of identifying research priorities for studying the contributions of biodiversity to people and how these contributions might be impacted by environmental change. Five main groups of questions emerged: (1) Enhancing the quantity, quality, and availability of biodiversity data; (2) Integrating different knowledge systems; (3) Improved methods for integrating diverse data; (4) Fundamental questions in ecology and evolution; and (5) Multi-level governance across boundaries. We discuss the need for increased capacity building and investment in research programmes to address these challenges.